The early inflammatory response after flexor tendon healing: A gene expression and histological analysis. Issue 5 (24th January 2014) - Manning, Cionne N.; Havlioglu, Necat; Knutsen, Elisa; Sakiyama‐Elbert, Shelly E.; Silva, Matthew J.; Thomopoulos, Stavros; Gelberman, Richard H.
ABSTRACT Despite advances in surgical techniques over the past three decades, tendon repairs remain prone to poor clinical outcomes. Previous attempts to improve tendon healing have focused on the later stages of healing (i.e., proliferation and matrix synthesis). The early inflammatory phase of tendon healing, however, is not fully understood and its modulation during healing has not yet been studied. Therefore, the purpose of this work was to characterize the early inflammatory phase of flexor tendon healing with the goal of identifying inflammation‐related targets for future treatments. Canine flexor tendons were transected and repaired using techniques identical to those used clinically. The inflammatory response was monitored for 9 days. Temporal changes in immune cell populations and gene expression of inflammation‐, matrix degradation‐, and extracellular matrix‐related factors were examined. Gene expression patterns paralleled changes in repair‐site cell populations. Of the observed changes, the most dramatic effect was a greater than 4, 000‐fold up‐regulation in the expression of the pro‐inflammatory factor IL‐1β. While an inflammatory response is likely necessary for healing to occur, high levels of pro‐inflammatory cytokines may result in collateral tissue damage and impaired tendon healing. These findings suggest that future tendon treatment approaches consider modulation of the inflammatory phase of healing. © 2014 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 32:645–652, 2014.